How to improve the reading levels of second language students in an international setting? - Lloyd, Alison (2016)
This paper aims to present the findings of a participatory action research project that was completed within a primary school setting. Three main themes run throughout this paper. Firstly, this study was done to find ways in which the reading levels of EAL pupils, who do not have access to English at home, can be improved. Secondly, the paper outlines the use of a participatory action research approach to initiating change within one’s own setting. Central to this issue, the paper aims to illuminate the effects that one’s leadership approach can have on the validity and success of the change. Following the ripple effect model through its phases, and using a focus group approach, the paper intends to add to the body of work surrounding leading change, action research and EAL learners in schools. This paper concluded that, with the use of online reading support and lunch time interventions, one can lead a change to improve the reading levels of children who do not have access to English at home.